Lignin: composition, synthesis and evolution - Maceda, Agustín; Soto-Hernández, Marcos; Peña-Valdivia, Cecilia B.; Trejo, Carlos; Terrazas, Teresa (Instituto de Ecología, A.C., 2021)
Lignin is one of the main structures of the cell wall of plants and its composition varies between taxonomic groups. The objective of this study was to review the structure of lignin, the process of lignification and the proposals of evolutionary patterns of its evolution. For this, the existing literature was reviewed, each point was analyzed and explained to finally propose an evolutionary hypothesis of the lignification process in angiosperms. Lignin is composed of various monomers and polymers, its biosynthesis occurs in plastids and endoplasmic reticulum, to subsequently polymerize through different enzymatic groups in the cell wall, where the cooperative lignification process occurs. During the evolution of plants, the genetic and enzymatic systems for the biosynthesis of lignin were developed. The two main types of lignin that accumulate in the tracheary elements of plants are guayacil-type lignin and syringyl/guayacil type lignin. The presence of syringyl in Isoetes, Selaginella, Lycophyta and algae species due to evolutionary convergence conferred resistance to pathogens and UV rays. The occurrence of catalytically functional promiscuous enzymes led to the appearance of lignin, suberine and cutin; in addition, the anatomical and chemical diversification of the cell wall in angiosperms allowed their distribution in different environmental conditions.